Pengaruh Kreativitas dan Inovasi terhadap Keputusan Pembelian di Maketplace Shopee (Studi Kasus Pada Mahasiswa Institut Stiami Angkatan 2017-2020) - Melsa Anindia Devika; Muhammad Akbar; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect of Creativity and Innovation on Purchase Decisions in the Shopee marketplace among students of STIAMI Institute, Class 2017 -2020. The research method used is a quantitative method. Data collection was carried out using a questionnaire technique which was measured using a Likert scale. The population of this study was the 2017- 2020 STIAMI Institute students, totaling 9114 and a sample consisting of 100 Shopee user respondents. The data analysis used in this research were descriptive percentage analysis and multiple linear regression analysis with the help of IBM SPSS Statistics Version 24 program. The results show that: (1) Creativity has a positive and significant effect on Purchase Decisions with a value of 44.2%; (2) Innovation has a positive and significant effect on Purchase Decisions with a value of 53.7%; (3) Creativity and Innovation simultaneously have a positive and significant effect on Purchase Decisions with a value of 55.2%, with the remaining 44.8% being the influence of other factors not examined in this study.